2020
DOI: 10.1186/s13018-020-02086-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the early clinical outcomes of arthroscopic debridement in the treatment of shoulder tuberculosis

Abstract: Background Due to atypical clinical symptoms, it is difficult to diagnose joint tuberculosis infection, which often results in misdiagnosis and missed diagnosis. It is easy to cause joint disability. And there are few reports of using arthroscopy to diagnose and treat shoulder tuberculosis. This case series aims to introduce the clinical outcomes of arthroscopic treatment of shoulder tuberculosis. Methods Twenty-nine patients with shoulder tuberculosis from September 2013 to February 2019 were included (10 ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…20,21 Both open surgery and minimal invasive arthroscopy have been reported as the debridement procedures for joint TB in the literature. 7,22,23 Moon et al 24 reported open surgical debridement or synovectomy combined with postoperation immobilization to treat pediatric HTB, with a good result of 73.1%. Tiwari et al 25 described hip arthroscopy as an effective and safe minimally invasive procedure in the treatment of pediatric HTB, which seemed to have more advantages in earlier return to activity, less invasive and less perioperative morbidity when compared with the open procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Both open surgery and minimal invasive arthroscopy have been reported as the debridement procedures for joint TB in the literature. 7,22,23 Moon et al 24 reported open surgical debridement or synovectomy combined with postoperation immobilization to treat pediatric HTB, with a good result of 73.1%. Tiwari et al 25 described hip arthroscopy as an effective and safe minimally invasive procedure in the treatment of pediatric HTB, which seemed to have more advantages in earlier return to activity, less invasive and less perioperative morbidity when compared with the open procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A delayed intervention may lead to more severe damage of bone and cartilage, subluxation, or ankylosis 20,21. Both open surgery and minimal invasive arthroscopy have been reported as the debridement procedures for joint TB in the literature 7,22,23. Moon et al24 reported open surgical debridement or synovectomy combined with postoperation immobilization to treat pediatric HTB, with a good result of 73.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic shoulder surgery (ASS) is a commonly used procedure for shoulder surgery with minimal invasiveness, a wide field of vision, and rapid functional recovery ( 1 , 2 ). Despite the popularity of the surgery, the severe postoperative pain becomes a complication after ASS (up to 45%) that prolongs the patient’s recovery period and seriously affect the quality of life ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASA, American Society of Anesthesiologists; PCA, Patient controlled analgesia; PACU, Post anesthesia care unit; GA, General anesthesia; VAS, Visual analog scale; NRS, numerical rating scale; O, Opioids consumption;[1], Horner syndrome;[2], Dyspnea;[3], Hoarseness;[4], Vomiting and nausea.…”
mentioning
confidence: 99%